Anti-restenotic and anti-thrombotic effect of polymer-free N-TiO2 film-based tacrolimus-eluting stent in a porcine model. (March 2020) - Park, Dae Sung; Bae, In-Ho; Jeong, Myung Ho; Lim, Kyung-Seob; Hong, Young Joon; Shim, Jae Won; Kim, Jae Un; Kim, Mun Ki; Kim, Jung Ha; Hyun, Dae Young; Park, Jun-Kyu; Lim, Han Chul; et al.
Abstract: A polymer-based coronary drug-eluting stent might induce inflammation and stent thrombosis of the vessel wall due to the presence of the polymer. Therefore, the purpose of this study was to compare synthetic poly lactic–glycolic acid (PLGA)-based tacrolimus (TCL)-eluting stents (PLGA-TES) and polymer-free TCL-eluting stents (PF-TES) in in vitro and in vivo models. The PF-TES was deposited with a TiO2 thin film onto a bare metal stent (BMS) using plasma-enhanced chemical vapor deposition (PECVD). The surface morphologies of the stents were investigated by scanning electron microscopy and energy dispersive X-ray spectroscopy methods. The effect of the drugs released from the stents on smooth muscle cell (SMC) proliferation and platelet adhesion were examined. Animal studies were performed with four study groups; 1) BMS, 2) N-TiO2, 3) PLGA-TES, and 4) PF-TES. Further, after 4 weeks of implantation, the vessels surrounding the stents were isolated and then subjected to various analyses. In this study, the stent was deposited with a very thin and uniform TiO2 film. The platelet adhesion on the TiO2 surfaces was less than that on the BMS surface. The drug was uniformly coated on the stent surface with a concentration of 1.184 μg/mm 2 . SMC proliferation was significantly inhibited in the TCL-eluting stent group (62.8 %, 42.3 %, n = 7, p < 0.05, respectively). In the animal study, the percent area restenosis was significantly decreased in the PF-TES group compared with that in the BMS group (BMS: 41.1 ± 11.27 % vs. PF-TES: 22.3 ± 7.02 % n = 10, p < 0.05). In particular, the fibrin score was lower in PF-TES group compared with that in the PLGA-TES group (PF: 1.3 ± 0.27 vs. PLGA-TES: 1.9 ± 0.53, n = 10, p < 0.05). The introduction of TiO2 deposition during fabrication of PF-TES might be an efficient process to prevent in-stent restenosis and thrombosis.